Redescription of Micaria beaufortia (Araneae, Gnaphosidae), with notes on Afrotropical Micaria - Marusik, Yuri M.; Omelko, Mikhail M. (Zootaxa, 2017)
Three species of Micaria Westring, 1851 are known to occur in the Afrotropical Region, two from Namibia and one from South Africa. All three species are known from a single sex only, either from the male (M. tersissima Simon, 1910) or from the females in the case of M. beaufortia (Tucker, 1923) and M. chrysis (Simon, 1910). In this paper, we redescribe the female of M. beaufortia and describe the previously unknown male of this species. This species has pseudosegmented tarsi and complex scopula formed by two paired rows of setae; these characters are unknown in other Micaria. The setae covering the legs in M. beaufortia are briefly described and the scopula is compared with that of M. fulgens (Walckenaer, 1802). A paired mating plug, previously unknown in Micaria, is documented in M. beaufortia. It was found that M. chrysis and M. tersissima, considered in the World Spider Catalog (2017) as endemics of Namibia, were actually described from Northern Cape Province, South Africa. The taxonomic position of these two species is briefly commented on and distribution records of all three species are mapped.